Differences in β‐cell function and insulin secretion in Black vs. White obese adolescents: do incretin hormones play a role?. Issue 2 (22nd January 2016) - Michaliszyn, Sara F; Lee, SoJung; Bacha, Fida; Tfayli, Hala; Farchoukh, Lama; Mari, Andrea; Ferrannini, Ele; Arslanian, Silva
Abstract : Black youth are at higher risk for type 2 diabetes (T2D) than their White peers. Previously we demonstrated that for the same degree of insulin sensitivity, Black youth have an upregulated β‐cell function and insulin hypersecretion, in response to intravenous (iv) glucose, compared with Whites. To investigate if the same holds true during an oral glucose challenge and because of the important role of glucagon‐like peptide 1 (GLP‐1) and glucose‐dependent insulinotropic polypeptide (GIP) in augmenting insulin secretion, we examined β‐cell function and incretin hormones in 85 Black and 78 White obese adolescents, with normal glucose tolerance (NGT), during a 2‐h oral glucose tolerance test (OGTT) with mathematical modeling of plasma glucose and C‐peptide concentrations to assess β‐cell glucose sensitivity (βCGS), rate sensitivity, potentiation factor, and insulin sensitivity. Incretin, pancreatic polypeptide, and glucagon concentrations were measured during the OGTT. Black obese youth had a heightened early insulin secretion together with significantly greater βCGS, rate sensitivity, and potentiation factor compared with Whites, with no differences in incretin and glucagon concentrations. Basal and stimulated insulin clearance was lower (p = 0.001) in Black vs. White youth. In conclusion, during an OGTT Black obese youth with NGT demonstrate a pronounced early insulin secretion jointly with heightened β‐cell glucose sensitivity, rate sensitivity, and potentiation factor. These racial disparities in β‐cell function and the pathophysiological components of T2D are unlikely to be attributed to incretin hormones and remain to be investigated further to explain the metabolic basis for the enhanced risk of T2D in back youth.